Diachronous collision in the Seve Nappe Complex: Evidence from Lu–Hf geochronology of eclogites (Norrbotten, North Sweden) - Fassmer, Kathrin; Bukała, Michał (Journal of Metamorphic Geology, 2021)
Agentúra na Podporu Výskumu a Vývoja, Grant/Award Number: APVV-18- 0107; Deutsche Forschungsgemeinschaft, Grant/ Award Number: FR700/18-1 We thank Christopher Barnes (AGH University of Science and Technology, Kraków) for providing us with some of the studied samples. Kathrin Fassmer thanks Svenja Trapp and Matthias Hauke (University of Bonn) for help during Lu–Hf laboratory work. We would also like to thank M. Smit, F. Corfu and A. Kylander-Clark for their reviews which greatly contributed to improving the manuscript. This research was funded by DFG-Grant FR700/18-1 to N. F. and the Slovak Research and Development Agency project APVV-18- 0107 to M.J, and partially supported by the National Science Centre (Poland) project 2014/14/ST10/00321 to J. Majka. M.Bukała acknowledges The Polish National Agency for Academic Exchange for the scholarship no. PPN/ IWA/2018/1/00046/U/0001. This is contribution no. 64 of the DFG-funded LA-ICP- MS Laboratory at the Institute for Geosciences, University of Bonn, Germany. The collision of Baltica and Laurentia during the Caledonian Orogeny happened at c. 400-420 Ma. However, subduction and collision processes also took place before this main collisional phase and the tectonic history of these is still not fully resolved. The Seve Nappe Complex in Sweden has recorded these earlier phases. The Seve Nappe Complex in Norrbotten (North Swedish Caledonides) comprises four superimposed nappes emplaced by eastward thrusting (from base to top according to the conventional structural interpretation): Lower Seve Nappe, Vaimok, Sarek, and Tsakkok Lenses. Eclogites occur in the Vaimok and Tsakkok Lenses. The Vaimok Lens represents rocks of the Baltican continental margin intruded by Neoproterozoic dolerite dikes which were later eclogitized and boudinaged. By contrast, eclogites of the Tsakkok Lens are former oceanic basalts associated with calcschists, possibly representing the ocean-continent transition between Baltica and Iapetus. Previous age determinations for eclogitization yielded ...